A systematic review about telemedicine in orthopedics - Petersen, Wolf (Arch Orthop Trauma Surg, 2021)
PURPOSE: Until now, the use of telemedical applications in orthopedics was limited to sparsely populated countries. However, due to the SARS-CoV-2 pandemic, interest in orthopedics in these procedures has increased significantly. The aim of this systematic review was to find out to what extent there is scientific evidence for the use of telemedicine in the orthopedic field. METHODS: A systematic literature search was carried out in various databases on randomized controlled trials (RCTs) on telemedical applications in orthopedics. RESULTS: Altogether, 14 articles were identified that reported about a total of eight RCTs of telemedical applications in orthopedics. Two RCTs were about a patient-to-doctor video consultation and six RCTs were about telerehabilitation after knee and hip arthroplasty (4 × knee arthroplasty, one hip and knee arthroplasty, one hip arthroplasty). For the majority of outcome parameters evaluated, there were no significant differences between the study groups. The cost effectiveness of videoconsultations depended on the workload (number of patient consultations) as well as the effectiveness of telerehabilitation on the distance of the patient's home to the health care center (30 km round-trip). CONCLUSION: There is sufficient evidence to recommend the use of telemedical methods in orthopedics. However, more research is necessary to further expand the possibilities of telemedical methods with regard to physical examination.